Bleeding in acute coronary syndromes and percutaneous coronary interventions: position paper by the Working Group on Thrombosis of the European Society of Cardiology - Steg, Philippe Gabriel; Huber, Kurt; Andreotti, Felicita; Arnesen, Harald; Atar, Dan; Badimon, Lina; Bassand, Jean-Pierre; De Caterina, Raffaele; Eikelboom, John A.; Gulba, Dietrich; Hamon, Martial; Helft, Gérard; et al. (European heart journal, 2011)
Bleeding has recently emerged as an important outcome in the management of acute coronary syndromes (ACS), which is relatively frequent compared with ischaemic outcomes and has important implications in terms of prognosis, outcomes, and costs. In particular, there is evidence that patients experiencing major bleeding in the acute phase are at higher risk for death in the following months, although the causal nature of this relation is still debated. This position paper aims to summarize current knowledge regarding the epidemiology of bleeding in ACS and percutaneous coronary intervention, including measurement and definitions of bleeding, with emphasis on the recent consensus Bleeding Academic Research Consortium (BARC) definitions. It also provides an European perspective on management strategies to minimize the rate, extent, and consequences of bleeding. Finally, the research implications of bleeding (measuring and reporting bleeding in trials, the importance of bleeding as an outcome measure, and bleeding as a subject for future research) are also discussed.